2015
DOI: 10.1590/1807-3107bor-2015.vol29.0028
|View full text |Cite
|
Sign up to set email alerts
|

Strain analysis of different diameter Morse taper implants under overloading compressive conditions

Abstract: The aim of this study was to evaluate the amount of deformation from compression caused by different diameters of Morse taper implants and the residual deformation after load removal. Thirty Morse taper implants lacking external threads were divided into 3 groups (n = 10) according to their diameter as follows: 3.5 mm, 4.0 mm and 5.0 mm. Two-piece abutments were fixed into the implants, and the samples were subjected to compressive axial loading up to 1500 N of force. During the test, one strain gauge remained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In two previous strain gauge analyses, it was reported that a vertical 1500 N load yielded the same strain at the implant neck as a 30 • angle 50 N load. Both experiments recorded 600 µs at the implant necks [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…In two previous strain gauge analyses, it was reported that a vertical 1500 N load yielded the same strain at the implant neck as a 30 • angle 50 N load. Both experiments recorded 600 µs at the implant necks [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…In light of this, the increase in retention force after thermomechanical aging is thought to be caused by mechanical adaptation and cold fusion that occurred between the unsmooth surfaces of the abutments and caps as a result of pressure applied by 1200,000 mechanical cycles in the chewing simulator machine. Castro et al 28 employed a strain gauge and observed that compressive loading result in strain around the internal and external walls of the cervical regions of Morse taper implants. The strain was affected by the diameter of the Morse taper implants, with narrow implants subjected to more strain.…”
Section: Discussionmentioning
confidence: 99%
“…Complex strain fields around fixtures, implant components, or suprastructures could be typically measured using strain gauge analysis (Abduo, Bennani, Lyons, Waddell, & Swain, ; Abreu et al, ; Asvanund, ; Castro, Zancope, Verissimo, Soares, & Neves, ; Cehreli & Iplikcioglu, ; Cho et al, ; De Vasconcellos et al, ; De Vasconcellos, Nishioka, de Vasconcellos, Balducci, & Kojima, ; Heckmann et al, ; Hegde et al, ; Isidor, ; Karl, Rosch, Graef, Talyor, Heckmann, ; Karl, Graef, & Wichmann, ; Karl, Graef, Wichmann, & Krafft, ; Karl & Holst, ; Karl & Taylor, ; Karl, Wichmann, Heckmann, & Krafft, ; Nishioka, de Vasconcellos, & de Melo Nishioka, ; Nishioka, de Vasconcellos, Joias, & Rode Sde, ). With this method, an electrical resistance in the strain gauge enables the measurement of deformation with high sensitivity (μm/m) (Asvanund, ).…”
Section: Introductionmentioning
confidence: 99%